2021
DOI: 10.3390/foods10102453
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Helicobacter pylori Activity of a Lactobacillus sp. PW-7 Exopolysaccharide

Abstract: Helicobacter pylori is a cause of gastric cancer. We extracted the exopolysaccharide (EPS) of Lactobacillus plajomi PW-7 for antibacterial activity versus H. pylori, elucidating its biological activity and structural characteristics. The minimum inhibitory concentration (MIC) of EPS against H. pylori was 50 mg/mL. Disruption of the cell membranes of pathogenic bacteria by EPS was indicated via the antibacterial mechanism test and confirmed through electron microscopy. EPS also has antioxidant capacity. The IC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Similarly, HePS produced by L. gasseri [35] and L. kefiranofaciens DN1 [36] have shown in vitro antibacterial activity against several foodborne pathogens, such as Listeria monocytogenes and Salmonella enteritidis. Moreover, in a recent study, HePS extracted from L. plajomi PW-7 (formerly Lactobacillus plajomi) showed antibacterial activity against H. pylori, S. aureus, and E. coli [37]. With respect to the potential inhibitory mechanism of pathogenic bacteria by EPS, it was proposed that this can be effected by disrupting the integrity of membranes and releasing the contents of soluble proteins [38].…”
Section: Antimicrobial Effectsmentioning
confidence: 99%
“…Similarly, HePS produced by L. gasseri [35] and L. kefiranofaciens DN1 [36] have shown in vitro antibacterial activity against several foodborne pathogens, such as Listeria monocytogenes and Salmonella enteritidis. Moreover, in a recent study, HePS extracted from L. plajomi PW-7 (formerly Lactobacillus plajomi) showed antibacterial activity against H. pylori, S. aureus, and E. coli [37]. With respect to the potential inhibitory mechanism of pathogenic bacteria by EPS, it was proposed that this can be effected by disrupting the integrity of membranes and releasing the contents of soluble proteins [38].…”
Section: Antimicrobial Effectsmentioning
confidence: 99%
“…Referring to the view of Nikhita [ 35 ], the effect of enzymolysis time on antioxidant activity was studied with DPPH scavenging rate as an index to determine the highest productivity. The reaction solution was composed of 0.1 mL sample solution with different enzymatic hydrolysis times and 0.1 mL DPPH (0.1 mM, prepared in ethanol solution), and the absorbance at 517 nm was measured after being placed in a dark environment for 30 min [ 49 ]. The unezymolytic mussel sample was used as a blank control.…”
Section: Methodsmentioning
confidence: 99%
“…The lyophilized powder of Y-1 enzymolysis product was prepared in an aqueous solution at concentrations of 10, 20, 30, 40, and 50 mg/mL. The DPPH radical scavenging activity, superoxide anion radical scavenge activity, hydroxyl radical scavenge activity and determination of reducing power of the solution that was tested refer to previous articles [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…The research found that the extracellular polysaccharides produced by Lactobacillus sp. PW-7 isolated from fermented pickles can inhibit H. pylori [ 83 ]. Studies have shown that consuming kimchi can inhibit the growth of H. pylori in H. pylori -infected C57BL/6 mice [ 84 ].…”
Section: Health Benefits Of Fermented Vegetablesmentioning
confidence: 99%